A carved ivory cylinder from Akchakhan-kala, Uzbekistan: Problems of dating and provenance. (February 2016) - Betts, Alison; Dodson, John; Garbe, Ulf; Bertuch, Fiona; Thorogood, Gordon
Abstract: Excavations at Akchakhan-kala in Uzbekistan, a region known in antiquity as Chorasmia, recovered a large, elaborately carved and heavily burned cylinder of some very solid material. Its poor condition made identification of the raw material difficult. Here we used neutron tomography to examine the internal structure in a non-destructive way, and X-ray Diffraction to determine the main chemical composition of the material which confirmed it as ivory. This was followed by preparation for stable isotope and radiocarbon analysis. The stable isotope analysis suggests a tropical or subtropical grassland source for the ivory, which is unlikely to be from Uzbekistan. The dating shows the ivory to be much earlier than the context in which it was found. Whatever its origin, the ivory travelled far to reach Chorasmia, perhaps in its raw state, and perhaps also for some time in its carved form.